Enteropathogenic Bacterial and Intestinal Parasitic Infections among Asymptomatic Food Handlers in Rangsit University Canteens, Central Thailand - Sirima Kitvatanachai; Bajaree Jantrapanukorn; Utsanee Supcharoengoon; Chalirmporn Atasilp (Journal of Parasitology Research)
Food handlers play an important role in the transmission of foodborne diseases. 108 asymptomatic food handlers work in RSU canteens and have never been checked for intestinal bacteria and parasites, which might be a potential source of infection for customers. This study is aimed at estimating the prevalence of enteropathogenic bacterial and intestinal parasitic infections among food handlers in Rangsit University canteens, central Thailand. A total of 79 food handlers were enrolled, and each provided one stool sample (response rate of 73.2%). Females comprised 93.7% of study participants, and the largest age group was 41–50 years (34.2%). The prevalence of enteropathogenic bacteria in stool cultures was 2.5%, and only Aeromonas spp. were detected. The pathogenic protozoa Giardia duodenalis was detected in 1.3% of samples, and nonpathogenic protozoa was found in 11.4%. No helminths were found in any samples. Approximately 80% of food handlers demonstrated good hygiene practices, including regular hand washing after visiting the toilet, regular hand washing when preparing food, using soap when washing hands, wearing uniforms/gowns, practicing correct hand washing techniques, and having short fingernails. However, the results showed a lack of personal hygiene training and routine medical care (>50% of samples). Stronger intervention would help to eliminate future infections.